(untitled) (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2024)
A comprehensive study was conducted to develop a two-dimensional mathematical model for a thermal storage tank containing internal disk-shaped obstacles. This model, incorporating appropriate initial and boundary conditions, was solved using the built-in solvers of the licensed COMSOL Multiphysics 5.6 software. The COMSOL model demonstrated a maximum deviation of 2.2% from experimental results and even smaller discrepancies compared to ANSYS Fluent, validating its accuracy in describing the charging and discharging processes of a sensible heat storage tank with internal obstacles. Using this validated algorithm, numerical studies were performed to analyse temperature distribution and performance indicators for three distinct tank configurations. Among these configurations, the storage tank with a middle disk consistently exhibited superior performance. This tank achieved the highest mixing efficiency, as evidenced by smoother variations in the Richardson number and a more uniform temperature distribution. It also attained the highest capacity ratio (90.12%) and exergy efficiency (81.67%), indicating its effectiveness in heat retention and the quality of stored thermal energy. Furthermore, it demonstrated the highest charging efficiency at 67.51%, highlighting its ability to store incoming heat more effectively. These findings establish the tank with a middle disk as the most efficient configuration for thermal energy storage and uniform temperature distribution.